The Verse of Al-Dhar in Surat Al-A’raf according to Al-Hakim Al-Jashmi in his Interpretation of Al-Tahdheeb: A Comparative Analytical Study - Al-Sawa'da, Muhammad Mahmoud Falah (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The research aims to study the position of Al-Hakim Al-Jashmi in his interpretation (Al-Tahdheeb) and to analyze his sayings related to the meaning of the verse of Surat Al-A’raf in where God Almighty took the covenant from the descendants of Adam; The study also aims to compare his views with those of other scholars and determine the most accurate interpretation. Methods: The research relied on the analytical and comparative method to achieve the desired results. The words of Al-Jashmi were used to interpret the verse, and then they were discussed, analyzed, and compared with the views of other commentators. Results: The research concluded that accepting the narrations contained in the interpretation of the verse of Al-Dhar in general is the best approach in revealing its meaning. It is important to note that Al-Jashmi's approach to interpreting the verse is highly valid. Conclusions: Some commentators have caused confusion in the interpretation of the verse of Al-Dhar in Surat Al-Araf by accepting the narrations contained in it, which Al-Jashmi rejected. He believed that it is not suitable for an interpretation of the verse, following the Mu'tazili approach in dealing with novels and sayings.